2022
DOI: 10.1021/acs.analchem.2c03313
|View full text |Cite
|
Sign up to set email alerts
|

Transient Incomplete Separation of Species with Close Diffusivity to Study the Stability of Affinity Complexes

Abstract: Large molecules can be generically separated from small ones, though partially and temporarily, in a pressure-driven flow inside a capillary. This transient incomplete separation has been only applied to species with diffusion coefficients different by at least an order of magnitude. Here, we demonstrate, for the first time, the analytical utility of transient incomplete separation for species with close diffusion coefficients. First, we prove in silico that even a small difference in diffusivity can lead to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…First, we showed that ACTIS is inherently accurate, and this accuracy is invariant to large variations in geometries of the fluidic system and the flow. , Second, this insensitivity to variations, in turn, allowed us to create a simple and robust fluidic system, which supports ACTIS accuracy . Third, we showed ACTIS to be applicable to protein–small molecule and protein–aptamer binding pairs. , Although ACTIS can potentially be used for all molecular complexes, including protein–protein binding pairs, future experimental work needs to be done to show such applicability. Until now, ACTIS has lacked a practical data processing workflow.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…First, we showed that ACTIS is inherently accurate, and this accuracy is invariant to large variations in geometries of the fluidic system and the flow. , Second, this insensitivity to variations, in turn, allowed us to create a simple and robust fluidic system, which supports ACTIS accuracy . Third, we showed ACTIS to be applicable to protein–small molecule and protein–aptamer binding pairs. , Although ACTIS can potentially be used for all molecular complexes, including protein–protein binding pairs, future experimental work needs to be done to show such applicability. Until now, ACTIS has lacked a practical data processing workflow.…”
mentioning
confidence: 83%
“…Third, we showed ACTIS to be applicable to protein−small molecule and protein−aptamer binding pairs. 8,13 Although ACTIS can potentially be used for all molecular complexes, including protein−protein binding pairs, future experimental work needs to be done to show such applicability. Until now, ACTIS has lacked a practical data processing workflow.…”
mentioning
confidence: 99%
“…BSA−fluorescein equilibrium mixtures (EMs) were prepared with the strategy of "new sample-preparation workflow" that was introduced in our previous work. 2 In four ACTIS experiments, the fluorescein concentrations (L0) were fixed to be 0.07, 7.0, 70 and 210 µM, respectively (after correction based on the purity of fluorescein). For the ACTIS experiment with L0 = 0.07 µM, the total BSA concentrations (T0) in the EMs varied from 0 (lowest non-zero T0 = 1.0 µM) to 1000 µM with a total of 10 EMs with different T0 values.…”
Section: Supporting Informationmentioning
confidence: 99%
“…126,127 With the aid of computer simulation, Wang et al introduced a strategy named "Accurate Constant via Transient Incomplete Separation", which can serve as a reference method for characterizing the affinity of protein− aptamer binding in solution (Figure 3). 128 Strategies were also made for the determination of binding constants in strong complexation. 129,130 The authors demonstrated that the peak shape can be asymmetrical due to electromigration dispersion.…”
mentioning
confidence: 99%